A model of ceramic production, specialization and standardization of ceramic assemblages – on the basis of two sites from eastern Croatia belonging to Vučedol culture - Miloglav, Ina (2012)
The analysis of ceramic material from two Vučedol sites in eastern Croatia (Damića gradina at Stari Mikanovci and on Ervenica in Vinkovci) has enabled the reconstruction of Vučedol society viewed through its economic and technological segment, social organization and organization of production. Statistical test undertaken using coefficient of variation (CV) has shown a certain level of standardization of ceramic material which is particularly visible on bowls. The reason for greater level of standardization noticeable on a certain type of bowls shows that the bowls were being used more intensively and frequently in everyday life, which led to its faster wearing out, deformation and breaking, and consequently to its greater production and richer experience in its making. The production was taking place locally within the settlement, which is being confirmed by mineralogical-petrographic analyses and the method of X-ray diffraction done on ceramic fragments. The proposed model of organized production of ceramic products in Vučedol society would mean large-scale ceramic production which is still taking place within a household, and which is conditioned by greater commercial activity, increase of population, as well as social organization marked by stratification of society and emergence of hierarchic relationships.